The global educational policy environment in the fourth industrial revolution - Berman, Evan; Jules, Tavis Deryck 1980- (Public policy and governance)
Prelims -- Part I: re(framing) education governance -- Part II: educational mechanisms of governance -- Part III: modes of education governance -- About the authors -- Index